Suberoylanilide Hydroxamic Acid (SAHA) with Antioxidant vitamin E: Induces ER Stress Pathway in Human Cervical Cancer Cell Line - Sharma, Monal (Journal of Medical Biomedical and Applied Sciences, 2017)
Suberoylanilide hydroxamic acid (SAHA) is a targeted inhibitor of histone deacetylase, which has been reported to inhibit cell growth, induce apoptosis in a variety of tumor cells and shown to be an anti-cancer agent. This study describes the anti-tumor effect of SAHA alone and in combination with antioxidant vitamin E in human epithelial cervical cancer (HeLa) cells. Cell cycle analysis of drug HeLa cells showed slight decrease in cell population at the G1 phase, and increase at the G2/M Phase with concomitant decrease in S phase. We also observed SAHA induce anti-proliferative effect in a dose dependent manner and caused DNA fragmentation. Expression of CHOP and Bax/Bcl-2 Ratio were found to be augmented after post treatment. Level of Reactive oxygen species (ROS) was increased and antioxidant enzyme catalase activity was decreased after treatment, suggesting that SAHA induced apoptosis is an endoplasmic reticulum stress pathway. This study provides a better understanding of molecular mechanism of anti- tumor effect of SAHA and gives insight of the development of better undersigned combinatorial chemotherapy strategies.